PHYSIOLOGICAL AND CERTAIN BIOCHEMICAL RESPONSES OF RED KANDHARI BULLOCK WITH DIFFERENT BULLOCK CARTS (Indian Journal of Animal Production and Management, 2014)
Present study evaluated the physiological and biochemical responses of Red Kandhari bullock using three different kinds of bullock cart namely pneumatic, iron and wooden. Carting trials were carried out on three different road (Field road, Kaccha road, Tar road) using varying load (500, 750, 1000 kg). The physiological responses (respiration rate, heart rate and rectal temperature) were increased after carting depending upon load and road variables. However, blood glucose level was significantly depressed in iron and wooden bullock carts after carting when compared with the pre carting values. These findings indicated that physiological response and blood glucose level varies according to the work load, road and carting conditions in Red Kandhari bullocks.
Keywords: Bullock cart; Draft; Physiological response; Glucose